Improving Learning Outcomes in Mathematics Using the Talking Stick Learning Model - Ilham Marnola; Lindu Sartika; Hilliyani Hilliyani; Yulia Rahmi; Siska Wahyuni (Indonesian Journal of Instructional Media and Model, 2022)
Measurement-related math subject is taught in Madrasah Ibtidaiyah, but many students still struggle to understand the concepts making the subject becomes boring and unappealing. Low learning outcomes in mathematics might be caused by boredom with the subject and problems in comprehending. The Talking Stick learning model is implemented to help students who are struggling with mathematics. This study sought to determine whether the Talking Stick learning model may improve learning outcomes in mathematics. This experimental study used quantitative methodology. The participants were third-graders at MIN 9 Aceh Tengah. A formative test with multiple choice questions was used as the data collection tool. The test was administered to both the experimental and control classes in two stages, namely the pretest (beginning test) and post-test (final test). The t-test was the analytical method utilized. The data demonstrated that the Talking Stick learning approach might be used to enhance learning outcomes in mathematics.